Role-play for undergraduate medical ethics education : a systematic mapping study - Mohd Salami Ibrahim
Background: The versatility and relatively low-cost of role-play that provides experiential learning could prove valuable for the undergraduate medical ethics education. However, a deficiency of research has left educators and policy makers with gaps of evidence for adopting role-play within the contemporary competency-based undergraduate medical ethics curriculum. Aims: This paper aims to explore research activities on role-play for undergraduate medical ethics education over the last ten years through systematic mapping. Additional focus was given on the fidelity of role-play's implementation and whether there were enough studies for the development of systematic reviews. Methods: Comprehensive searching was conducted between February and July 2017 based on a priori inclusion and selection protocol. Sources included six electronic databases, citation tracking of articles from a wide variety of sources, hand searching of unpublished theses and dissertations, internet websites, and conference papers and presentations. Results: 17 studies with a total of 2080 reported participants were included. The aims of the studies can be broadly grouped into measuring educational impact, descriptive curricular experience, factors influencing effectiveness and the cost effectiveness of role-play. Fidelity of implementation significantly varied between studies, with only two studied populations demonstrating the full features of this important aspect of role-play. A total of five randomised quantitative studies and three studies with in-depth qualitative analyses were likely viable for further aggregative and configurative systematic review. Conclusion: This systematic mapping found only a relatively small number of studies in this field since 2007, although there were potentially enough studies to conduct further systematic reviews. This study also recommends a change of strategy for future practice, policy and research to focus on the fidelity of implementation of role-play. This new strategy will better facilitate decisions on how to practically and effectively adopt role-play for undergraduate medical ethics education.